Evaluation of a novel mechanical compression device for hematoma prevention and wound cosmesis after CIED implantation. Issue 4 (4th March 2022) - Rojas, Edward; Morgaenko, Katerina; Brown, Louis; Kim, Sieu; Mazimba, Sula; Malhotra, Rohit; Darby, Andrew; Monfredi, Oliver; Mason, Pamela; Mangrum, James Michael; Haines, David E.; Campbell, Christopher; et al.
Abstract: Background: An important complication of cardiac implantable electronic devices (CIED) implantation is the development of hematoma and device infection. Objective: We aimed to evaluate a novel mechanical compression device for hematoma prevention and cosmetic outcomes following CIED implantation. Methods: An open, prospective, randomized, single‐center clinical trial was performed in patients undergoing CIED implantation. Patients were randomized to receive a novel mechanical compression device (PressRite, PR) or to receive the standard of care post device implantation. Skin pliability was measured with a calibrated durometer; the surgical site was evaluated using the Manchester Scar Scale (MSS) by a blinded plastic surgeon and the Patient and Observer Scar Scale (POSAS). Performance of PR was assessed through pressure measurements, standardized scar scales and tolerability. Results: From the total of 114 patients evaluated for enrollment, 105 patients were eligible for analysis. Fifty‐one patients were randomized to management group (PR) and 54 to the control group. No patients required early removal or experienced adverse effects from PR application. There were 11 hematomas (14.8% vs. 5.9% in the control and PR group respectively, p  = NS). The control group had higher post procedure durometer readings in the surgical site when compared with the PR group (7.50 ± 3.45 vs. 5.37 ± 2.78; p  = < .01). There were l ower MSS scores in the PR group after 2 weeks ( p  = .03). Conclusion: We have demonstrated the safety of PR application and removal. In addition, PR appears to improve postoperative skin pliability, which could facilitate wound healing.